If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 9) = -45 + 7 Reorder the terms: 2(9 + 4x) = -45 + 7 (9 * 2 + 4x * 2) = -45 + 7 (18 + 8x) = -45 + 7 Combine like terms: -45 + 7 = -38 18 + 8x = -38 Solving 18 + 8x = -38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 8x = -38 + -18 Combine like terms: 18 + -18 = 0 0 + 8x = -38 + -18 8x = -38 + -18 Combine like terms: -38 + -18 = -56 8x = -56 Divide each side by '8'. x = -7 Simplifying x = -7
| t^2(r-2)+1(r-2)= | | 2x-3(14+6x)=6 | | -3.5x+6.3=-0.3(9x-5) | | x-13=107 | | 7t-10+3t=-5t+3t | | 0.04(4c-44)=-0.8(c-5) | | 3x-8=-(17+2x) | | 3x+13=2173 | | y+5=-x/4 | | .12(x)=100000 | | 0.12y+0.09(y+2000)=1650 | | 8(y+5)-43= | | 6x-(16+2x)=2(x-1) | | x^2/x-3+x-12/x-3 | | =(3+7i)(8-2i) | | (6-y)(3y+4)=0 | | 4b-6-12b-3= | | -21-1/7n-5/7n | | 6/a+2/b | | 4t^2+6t-30=0 | | (50-b)-(3b+2)=0 | | 2x+9=1449 | | 12n+5/2-2n-3/2 | | 0.14+0.07(y+5000)=2240 | | f^2+11f+30=0 | | 2x^2-24+92=22 | | 4+4(-2)= | | -4=15+x | | X^2-15X-28=6 | | m^2-12m=-20 | | 4(-4)(-5)= | | 3x-2x=45 |